Vitamin D Levels in Women with Polycystic Ovary Syndrome - Sidabutar, Elida; Halim, Binarwan; Ganis Siregar, Muhammad Fidel; Lutan, Delfi; Adenin, Ichwanul; Kaban, Yostoto (KnE Medicine, 2016)
INTRODUCTION: Polycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of reproductive age. There is some evidence suggested that vitamin D played a role in the incidence of PCOS. Previous research has found vitamin D deficiency in the pathogenesis of PCOS and cohort studies showing the relationship of obesity with decreased levels of 25-hydroxy vitamin D. Therefore, we aim to conduct a study on vitamin D levels in women with polycystic ovary syndrome. OBJECTIVE: To determine the difference of the levels of vitamin D in women with and without polycystic ovary syndrome. METHODS: This study is a comparative analytical study on two unpaired population by using cross-sectional study design. The study was conducted in Halim Fertility Clinic Medan starting in November 2014 through April 2015. Blood samples were taken from 23 women PCOS and 23 non-PCOS women. Further data were tabulated and analyzed. RESULTS: Vitamin D levels are lower in women with PCOS compared to controls. In the PCOS group, the levels of vitamin D were lower in obese women. Vitamin D levels were also lower in PCOS women with WHR> 0.85. CONCLUSION: This study showed a significant lower level of vitamin D in PCOS patient.